The impact of implementing Aceh Qanun No. 11 of 2018 concerning Sharia Financial Institutions on the management of sharia insurance institutions - Simanjuntak, Indah; Sudiarti, Sri; Yanti, Nursantri (Universitas Islam Indonesia, 2023)
IntroductionArticle 65 of Aceh Qanun No. 11 of 2018 concerning Sharia Financial Institutions regulates that financial institutions operating in Nagroe Aceh Darussalam are required to make adjustments no later than three years from the promulgation of the qanun. PT Asuransi Sinarmas Syariah Banda Aceh is one of the financial institutions that is transitioning from conventional to sharia as the implementation of this qanun.ObjectivesThis research aims to find out the impact of implementing this Qanun on PT Asuransi Sinarmas Syariah Banda Aceh. MethodThis qualitative research uses interviews, observation, and documentation for data collection. The data is then reduced, simplified and presented to draw conclusions.ResultsThe results of the research show that there were changes in the payment mechanism carried out by PT Asuransi Sinarmas Syariah Banda Aceh before and after the implementation of the qanun. Apart from that, the implementation of the qanun caused PT Asuransi Sinarmas Syariah Banda Aceh to experience a decline in business of up to 70% in the initial stages. However, subsequently, PT Asuransi Sinarmas Syariah Banda Aceh began to experience an increase in business. ImplicationsThe sharia insurance industry in Nanggroe Aceh Darussalam needs to provide education and information about the implementation of the sharia system for the wider community.Originality/NoveltyThis research is unique because it contributes to the analysis of the impact of sharia legislation on the sharia insurance industry.